What is the best treatment for adult somatization disorder?. Issue 5 (May 2017) - Smith, Roxanne
Abstract : EVIDENCE‐BASED ANSWER : Psychological therapies, cognitive behavioral therapy (CBT), and enhanced care by the primary care physician (PCP) all have small positive effects in adults with somatization disorder (SOR: B, systematic review of low‐quality RCTs). Yet, when compared with enhanced care, psychological therapies generally were not more effective. SSRIs/SNRIs and St. John's wort have moderate positive effects in reducing the severity of physical symptoms (SOR: B, systematic review of lowquality RCTs).